The effectiveness of penalty takers' deception: A scoping review - Zheng, R.; van der Kamp, J.; Miller-Dicks, M.; Navia, J.; Savelsbergh, G. (Human Movement Science, 2023)
Attackers are supposed to take advantage of producing deceptive actions in competitive ball sports, particularly in penalty situations. We conducted a scoping review of the experimental literature to scrutinize whether penalty takers do indeed benefit from using deceptive actions in penalty situations, especially by increasing the likelihood to score a goal. Studies using video-based and in-situ tasks in which soccer and handball goalkeepers try to save a penalty were evaluated. Results showed that penalty takers' manipulation of spatial information available to the goalkeeper during deception (i.e., by using misleading and/or disguising actions) is less effective in in-situ than video-based studies. We argue that this difference occurs because goalkeepers adapt differently to the spatiotemporal constraints in the video-based and in-situ tasks. Goalkeepers appear to prioritize picking up spatial information in video-based tasks while prioritizing temporal information in-situ tasks. Therefore, the manipulation of spatial information appears to be less effective in the more representative in-situ studies than in video-based studies. In order to deceive, penalty takers are advised to manipulate temporal information during on-field penalty situations.